A mechanism of customizing learning programs for older adults' lifelong learning - Hidetsugu Suto; Qianran Wang (Adult Education Research Conference, 2023)
Many of the Asian countries are facing aging society problems, and lifelong learning is becoming more and more important. In order to provide the chances to join the learning programs for older adults, suitable learning programs must be provided. However, designing learning programs for older adults is not easy because they are in various physical and mental conditions. To approach the problem, the authors have proposed a mechanism for personalizing learning programs for older adults. In this paper, algorithm and data structures of the mechanism is explained, and examples of the results are shown.
Keywords: Personalization system; database system; Therblig